Integral involving aleph-function and the generalized incomplete hypergeometric function - (:unkn) unknown (Isik University, 2020)
The aim of this paper is to establish a general definite integrals involving product of the Aleph function and generalized incomplete hypergeometric function with general arguments. Being unified and general in nature, this integral yield a number of known and new results as special cases. For the sake of illustration, several corollaries are also recorded here as special case of our main results. © 2020, Isik University..
Keywords: Aleph-function; Generalized incomplete hypergeometric function; H-function; I-function